The intricate relationship between microtubules and their associated motor proteins during axon growth and maintenance - Prokop, Andreas (BioMed Central, 2013)
The hallmarks of neurons are their slender axons which represent the longest cellular processes of animals and which act as the cables that electrically wire the brain, and the brain to the body. Axons extend along reproducible paths during development and regeneration, and they have to be maintained for the lifetime of an organism. Both axon extension and maintenance essentially depend on the microtubule (MT) cytoskeleton. For this, MTs organize into parallel bundles that are established through extension at the leading axon tips within growth cones, and these bundles then form the architectural backbones, as well as the highways for axonal transport essential for supply and intracellular communication. Axon transport over these enormous distances takes days or even weeks and is a substantial logistical challenge. It is performed by kinesins and dynein/dynactin, which are molecular motors that form close functional links to the MTs they walk along. The intricate machinery which regulates MT dynamics, axonal transport and the motors is essential for nervous system development and function, and its investigation has huge potential to bring urgently required progress in understanding the causes of many developmental and degenerative brain disorders. During the last years new explanations for the highly specific properties of axonal MTs and for their close functional links to motor proteins have emerged, and it has become increasingly clear that motors play active roles also in regulating axonal MT networks. Here, I will provide an overview of these new developments.